IMPLEMENTASI FUNGSI BIROKRASI DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH (SUATU STUDI DI KECAMATAN LOLODA UTARA KABUPATEN HALMAHERA UTARA) - Tarinate, Dedi Dores (JURNAL ADMINISTRASI PUBLIK, 2014)
This study questioned the two main problems, namely: How does the process of implementation of the bureaucratic functions in the administration of local government and any constraint faced by the government in implementing the functions of bureaucracy. This study therefore aims to: (1) describe the implementation of the bureaucratic functions in the regional administration, especially in the northern Loloda districts on North Halmahera regency; (2) to identify obstacles or barriers faced by local governments in implementing bureaucratic functions, specialy on northern Loloda district of North Halmahera regency. This study used a descriptive-analytic method. The data and information collected by the technique of questionnaires distributed to 80 respondents and equipped with observation and documentation techniques then analyzed with descriptive analysis technique equipped with a secondary data analysis. Based on the analysis of data, it is known that: (1) the implementation of the public service has been running pretty good, although there are three indicators of public service functions that have not been optimally realized, such as discipline, responsibility and ability of service personnel. (2) there are three factors that are considered as constraint / barrier in the implementation of the bureaucratic functions of particular public service functions, namely: self-discipline, responsibility, and capacity / service personnel in providing services to the public. It can be concluded that the indicator function of public services such as discipline, responsibility and ability to care workers need to get the government's attention, for a fixed the public service for a better future. Keywords: bureaucracy function implementation, the regional administration